Spain : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Selected Issues paper analyzes household savings ratio in Spain. The household savings ratio has fallen to its lowest historical rate in 2012, as households cut back savings to support consumption in response to negative income shocks. Household savings fell across all households, but the declines were likely more material among lower income and highly indebted groups. Declining household income and savings slowed deleveraging and put household balance sheets under pressure. Looking ahead, households may need to restrain consumption further to free resources for repaying debt. Household savings rates will likely stay below historical levels for some time then slowly increase.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet